Reducing facet joint overload with a Kevlar-augmented lumbar disc replacement: An ex vivo investigation - Vanaclocha, V.; Atienza, C.; Vanaclocha, A.; Jorda-Gomez, P.; Peñuelas, A.; Medina-Ripoll, E.; Gómez-Pérez, A.; Saiz-Sapena, N.; Vanaclocha, L. (Clinical biomechanics (Bristol), 2025)
Facet joint overload often causes persistent low back pain after lumbar total disc replacement (TDR). This study is the first to test whether adding an anterior Kevlar band (K) can restore normal facet joint loading after lumbar TDR. We tested six human lumbosacral spines under four conditions: intact, after discectomy, with the ADDISC prosthesis, and with ADDISC plus Kevlar reinforcement. Facet joint pressures were measured at L3–L4, L4–L5, and L5–S1 during flexion, extension, lateral bending, and axial rotation. Discectomy caused a significant rise in facet pressures, especially during extension and axial rotation (p < 0.01). The ADDISC prosthesis lowered facet pressures but did not fully return them to baseline. Kevlar reinforcement lowered pressures by up to 35 % compared to the prosthesis alone, nearing intact spine levels, especially in flexion and extension. Kevlar reinforcement improves load distribution more than the prosthesis alone. It may help prevent facet degeneration and adjacent segment disease, offering a better biomechanical option for motion-preserving spine surgery. The combination of the ADDISC prosthesis and Kevlar reinforcement may help prevent facet joint degeneration and adjacent segment disease, potentially enhancing long-term outcomes in lumbar disc arthroplasty. [Display omitted] •Kevlar band reinforcement reduces facet joint pressure after lumbar disc replacement•ADDISC prosthesis improves pressure profiles vs. discectomy alone in cadaveric testing•Combined prosthesis and Kevlar band closely restore physiological facet load sharing•Highest joint pressures occurred in extension and axial rotation post-discectomy•Reinforcement may lower the risk of facet degeneration and adjacent segment disease